Pelayanan Kesehatan di Masa Pandemi Covid-19 pada RSUD dr. R. Goeteng Taroenadibrata Purbalingga - Emiraldo Win Pazqara; Lasyanti Lasyanti (Majalah Ilmiah Dinamika Administrasi (MIDA), 2022)
Writing this scientific paper aims to raise the discussion about health services in the era of the covid-19 pandemic at RSUD dr. R. Goeteng Taroenadibrata Purbalingga. The method used in this research is descriptive qualitative with data collection through interviews, observation and documentation. From the results of the analysis, several things can be confirmed including: first, from the tangible aspect, it shows the infrastructure at RSUD dr. R. Goeteng Taroenadibrata Purbalingga is good and adequate and supports the service process, even additional facilities are available to handle Covid-19 patients. Second, from the reliability aspect, the provision of providing health services tends to be slightly hampered due to the implementation of health protocol policies as a measure to anticipate the spread of COVID-19 in hospitals. Third, from the responsiveness aspect, the limitation of the number of employees due to the implementation of the health protocol affects the responsiveness of service delivery, so that an online service delivery mechanism is implemented through optimizing the utilization of the hospital website. Fourth, from the assurance aspect, the hospital continues to treat patients well but is adjusted to the adaptation of new habits/health protocols, including guaranteeing the ease of service through facilitation to interact through online services. Fifth, from the empathy aspect, it is shown through the hospital's commitment to provide the best service for both covid and non-covid patients without any difference in treatment.